Pembelajaran Data Science di Sekolah Dasar Terhadap Kemampuan Literasi Matematika Siswa - Agustiana, Anisa; Arisetyawan, Andika; Anusaen, Krittika (Jurnal Didaktika Pendidikan Dasar, 2023)
This research aims to determine the impact of data science learning on elementary school students’ mathematical literacy abilities. Data science has become an important aspect of today’s world of information and technology. Therefore, implementing data science learning at the elementary level can influence the mathematical literacy of students who are still in the early stages of learning. This research uses a qualitative approach with the SLR (Systematic Literature Review) method to collect, evaluate, and synthesize previous research and review the relationship between data science learning and students' mathematical literacy abilities at the elementary level. The research results show that data science learning can provide an increase in students' mathematical literacy at the basic level in the form of understanding mathematical concepts, data analysis, and problem-solving. However, several studies have also identified challenges in integrating data science learning into the elementary school curriculum. This research has contributed to developing more modern and relevant mathematics teaching strategies in an era that is increasingly connected to data.